Evaluation of physicochemical properties with the availability of plant nutrients in forests and crop farms in different Fijian provinces - Singh, Indra Raj; Nair, Pramod N (Plant Science Today, 2023)
Soils are the foundation of agriculture and forestry and it provides many functions such as the supply of water and nutrients and anchorage for plant growth and more. Forest farming and agriculture farming are 2 entities of the ecosystem and they may lead to changes in soil properties. To cope with the challenges in the soil management system, data on current chemical and physical soil properties are more necessary. Therefore, we present a comparative study on soil properties existing in soil and forest farms of Fiji Island. Soil samples from 24 different locations were collected from 8 sites based on the heterogeneity and land use of soils, keeping in view the variation in soil type and slope to determine physicochemical properties and nutrient status. The physical properties such as bulk density (1.05-1.20 Mg m-3), percent porosity (54.14-56.62), moisture % (16.78-18.53%) and soil permeability (11.79-12.35 cm hour-1 was comparatively higher in forest farms compared to the agricultural farms. The soil pH in forest farms and agriculture farms ranged from 5.42-6.10 and 5.30-5.61 respectively. A higher range of CEC was found in forest farms (17.7-19.2) may be due to the higher amount of soil organic matter in forest farms in comparison to agricultural farms. The results also showed that the nutrients such as N, P, K, Ca and Mg and micronutrients (Cu, Fe, Mn and Zn) values were low on the agricultural farms. The study suggests the combined use of good agricultural practices, limited use of agrochemicals and minimal soil disturbance at agriculture farms to prevent further degradation, acidification and nutrient stocks.